PERUBAHAN POLA REKRUITMEN CALON ANGGOTA LEGISLATIF PARTAI KEADILAN SEJAHTERA PASCA DITETAPKAN SEBAGAI PARTAI TERBUKA PADA PEMILU 2014 DI KOTA SEMARANG - Pratama, Satriyogi; ., Fitriyah; Adnan, Muhammad (Journal of Politic and Government Studies, 2014)
Recruitment politics or political representation plays an important role in the political system of a country with a democratic political system. Because the process is determining the people who will carry out the functions of the country's political system through existing institutions. Therefore, the goal is reached or not a good political system depends on the quality of political recruitment. This study aims to examine the change recruitment pattern of legislative candidate partai keadilan sejahtera of post defined as open party for 2014 election in semarang city. PKS recruitment mechanism is the formation of Regional Committee of the executor legisltaif candidate recruitment, socialization, Networking legislative candidates by a cadre member in each electoral district, verification of legislative candidates, internal elections plenary meeting by the committee and the board of DPD PKS and Determination of candidates for the Board legisltaif Regional Board PKS and the National Election Commission. Recruitment pattern adopted by the PKS is a semi-open pattern for all the people who qualify can be selected as candidates of the party. The society, unable to register in person to the Prosperous Justice Party, but a cadre of each electoral district will conduct a search on its territory, in the sense that the entire community has no right to register as a candidate member legisltaif. Keywords: Political Recruitment, Recruitment Mechanism and Patterns.